Surrendering to growth? The European Union's goals for research and technology in the Horizon 2020 framework. (1st October 2018) - Pollex, Jan; Lenschow, Andrea
Abstract: The European Union is one of the major global players in environmental protection and sustainability policy, and increasingly addresses themes such as human wellbeing, global justice and development. Grounded in the degrowth literature, this paper asks how the European Union measures progress, economic development and the relevance of environmental protection. Specifically, this article aims at tracing degrowth elements in the Horizon 2020 program, i.e. the research and innovation agenda and funding scheme of the Union, which constitutes one of the European Union's major instruments for steering economic development. Employing a frame analysis this research detects a minor agenda pointing beyond conventional growth perspectives; however, conventional growth remains the central focus in the Horizon 2020 framework even where "green growth" measures are discussed. This research shows that this pattern is especially evident in technology policy and schemes related to information and communication technology in particular. The article reflects on the rationales for why the European Union pursues only a minor degrowth agenda. It points to a neoliberal meta-frame and to the effects of path dependency related to the Union's common market conceived of as a driver of prosperity. Finally, the paper identifies comparative policy analysis as a promising area for deeper integration of degrowth theory in political science research.